High-z Stellar Masses Can Be Recovered Robustly with JWST Photometry - R. K. Cochrane; H. Katz; R. Begley; C. C. Hayward; P. N. Best (The Astrophysical Journal Letters)
Robust inference of galaxy stellar masses from photometry is crucial for constraints on galaxy assembly across cosmic time. Here, we test a commonly used spectral energy distribution (SED) fitting code using simulated galaxies from the S phinx ^20 cosmological radiation hydrodynamics simulation with JWST NIRCam photometry forward-modeled with radiative transfer. Fitting the synthetic photometry with various star formation history models, we show that recovered stellar masses are, encouragingly, generally robust to within a factor of ∼3 for galaxies in the range M _⋆  ∼ 10 ^7 −10 ^9 M _⊙ at z  = 5−10. These results are in stark contrast to recent work claiming that stellar masses can be underestimated by as much as an order of magnitude in these mass and redshift ranges. However, while >90% of masses are recovered to within 0.5 dex, there are notable systematic trends, with stellar masses typically overestimated for low-mass galaxies ( M _⋆  ≲ 10 ^8 M _⊙ ) and slightly underestimated for high-mass galaxies ( M _⋆  ≳ 10 ^9 M _⊙ ). We demonstrate that these trends arise due to the SED fitting code poorly modeling the impact of strong emission lines on broadband photometry. These systematic trends, which exist for all star formation history parameterizations tested, have a tilting effect on the inferred stellar mass function, with the number densities of massive galaxies underestimated (particularly at the lowest redshifts studied) and the number densities of lower-mass galaxies typically overestimated. Overall, this work suggests that we should be optimistic about our ability to infer the masses of high- z galaxies observed with JWST (notwithstanding contamination from active galactic nuclei) but careful when modeling the impact of strong emission lines on broadband photometry.